2012
DOI: 10.1186/1756-0500-5-247
|View full text |Cite
|
Sign up to set email alerts
|

Sense of coherence is associated with reduced psychological responses to job stressors among Japanese factory workers

Abstract: BackgroundJob stress is associated with adverse health effects. The present study was conducted to examine the association between sense of coherence (SOC), as advocated by Antonovsky, and psychological responses to job stressors among Japanese workers.MethodsA self-administered questionnaire containing a Japanese version of the 13-item SOC scale, the Brief Job Stress Questionnaire, and a self-rated health item were distributed to 1968 workers in X Prefecture. Anonymous responses were recovered by postal mail.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 23 publications
1
42
0
Order By: Relevance
“…Previous research indicated that SOC acts as a buffer for health against the negative effects of workload when evaluated by self-reported questionnaires 5,6,10) . Our data obtained using an index of objective workload indicated the safe finding.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research indicated that SOC acts as a buffer for health against the negative effects of workload when evaluated by self-reported questionnaires 5,6,10) . Our data obtained using an index of objective workload indicated the safe finding.…”
Section: Discussionmentioning
confidence: 99%
“…Job stress and job support were calculated using the Brief Job Stress Questionnaire (BJSQ), which is based on the demand-control-support model 10) . The BJSQ was developed in Japan for occupational health check-ups, and it is widely used there.…”
Section: Methodsmentioning
confidence: 99%
“…In a study of Japanese factory workers, SOC was associated with reduced psychological responses to stressors 31) . As new medical students perceive many stressors such as the first period of examinations, having a higher SOC score might reduce these stressors.…”
Section: Discussionmentioning
confidence: 99%
“…An association has been confirmed between SOC and biological mechanisms causing adverse physical health effects [32,33]. A strong sense of coherence as a personal characteristic serves as a buffer, protecting against the development of mental health problems and promoting psychological well-being [33][34][35] -having a strong SOC may reduce workers' negative job stress responses -tension, fatigue, anxiety, depression [36], the depletion of emotional resources, and feelings of depersonalization [37]. It is important to note that some epidemiological studies have confirmed a lower level of SOC in women population [30], also, the SOC level plays a more pronounced role in women's than in men's health under particularly stressful conditions [38].…”
Section: Introductionmentioning
confidence: 99%